The Reasons for the Percentage of Surplus Food Donations from Retail Markets to Food Banks and the Implications of their Relationship - Betz, Johanna (2016)
It is estimated that 25 percent of still edible food is sent to the landfill, even though worldwide millions of people suffer from hunger. With the growing world population, which is estimated to reach nine billion people during the middle of this century, and scarce resources (as land and water) for the food production food waste becomes a research area of more and more interest in the sector of sustainability. This is also because it is one of the United Nations’ Millennium Development Goals to stop hunger. Worldwide, food banks recover surplus food, which would otherwise become waste, from retail market donations and redistribute the recovered, still edible food to people in need. Unfortunately, only a minor percentage of the retail markets’ surplus food is eventually donated to food waste and therefore used for its original purpose – human intake. The aim of this dissertation is to find out the reasons for the percentage of surplus food donations to food banks. Former research pointed out, that research is needed to find out implications of the relationship between food banks and retail markets. The research for this dissertation found, that the percentage of surplus food donations from retail markets to food banks can be improved by up to 15 percent when the food banks would improve their collection schedule. However, there is a lack of communication and feedback in between food banks and retail markets which restrains a successful collaboration. The relationship and the collaboration to networking partners (as the media and the community) needs to be improved to achieve an effective and efficient partnership. Therefore, food banks need to become more innovative within their sector to enhance their public image and the attention of their stakeholders. It would also improve the relationship between food banks and retail markets when both parties are more aware of the implications of their collaboration. With an improved relationship food banks and retail markets can create shared value and common goals and make it a win-win situation for themselves, as well as for the triple bottom line of sustainability. An economic profit for the retail markets, increased by savings from the donations and a better reputation. The social support by the redistribution of food to people in need and the environmental aspects of preventing greenhouse gas emissions from decaying food, and not to waste scarce resources along the food supply chain. Furthermore, the ethical reasoning is addressed; not to waste food, while millions of people worldwide suffer from hunger.